2020
DOI: 10.1111/cei.13527
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of CXCL2 in ACPA-positive rheumatoid arthritis and its role in osteoclastogenesis

Abstract: Summary Anti-citrullinated protein/peptide antibodies (ACPA) play important roles in the pathogenesis of rheumatoid arthritis (RA). ACPA-positive (ACPA+) and ACPA-negative (ACPA−) RA were suggested to be different disease subsets, with distinct differences in genetic variation and clinical outcomes. The aims of the present study were to compare gene expression profiles in ACPA+ and ACPA− RA, and to identify novel candidate gene signatures that might serve as therapeutic targets. Comprehensive tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The major mediators of MSCs’ stimulatory effect towards osteoclastogenesis seemed to be IL-8/CXCL-8 and other CXCR-2 ligands (CXCL-1, -2 and -3). This is supported by previous in vitro studies reporting positive effects of these CXCL chemokines on monocytes migration and osteoclasts differentiation 36 38 . Given the complexity of MSCs’ secretome, these proteins may not be the only ones involved, and additional studies are warranted to identify additional players.…”
Section: Discussionsupporting
confidence: 87%
“…The major mediators of MSCs’ stimulatory effect towards osteoclastogenesis seemed to be IL-8/CXCL-8 and other CXCR-2 ligands (CXCL-1, -2 and -3). This is supported by previous in vitro studies reporting positive effects of these CXCL chemokines on monocytes migration and osteoclasts differentiation 36 38 . Given the complexity of MSCs’ secretome, these proteins may not be the only ones involved, and additional studies are warranted to identify additional players.…”
Section: Discussionsupporting
confidence: 87%
“…Since it has been reported that macrophages derived from the peripheral blood monocytes of RA patients produce inflammatory cytokines and chemokines after binding to the ACPA immune complex [ 22 ], abatacept-induced downregulation of CD64/FcγRI on monocytes may suppress ACPA immune complex-induced production of inflammatory cytokines/chemokines in patients with ACPA-positive RA. To test this hypothesis, peripheral blood monocytes were isolated from 19 RA patients who were ACPA-positive and treatment-naive and were cultured with ACPA immune complexes in the absence (mock) or presence of abatacept.…”
Section: Resultsmentioning
confidence: 99%
“…Later on, Krishnamurthy et al demonstrated that polyclonal ACPAs enhance osteoclast differentiation through a PADdependent IL-8-mediated autocrine loop [33]. A recent study also illustrated that ACPA-positive RA has a higher expression of CXCL2 (which can mediate the osteoclastogenesis in vitro) than ACPA-negative RA [34]. Monocyte lineage challenge with ACPA or RF autoantibodies can induce production of the cytokines TNF-α, IL-1β, IL-6, and IL-8 which are directly able to enhance osteoclast formation [35].…”
Section: Discussionmentioning
confidence: 99%